THE INFLUENCE OF THE APPEARANCE OF ENGLISHISM AND ENGLISH WORDS IN THE MEDIA ON THE USE OF ENGLISHISM IN EVERYDAY SPEECH IN SCHOOL-AGE CHILDREN (Heritage, 2020)
Everyday exposure to the influences of the English language in the Serbian-speaking environment naturally leads to a greater use of English words, which is manifested by the use of English as a substitute for words of the original Serbian language. The population that falls under the influence of a foreign, English language, among other groups of Serbian society, includes school-age children because they search for information of various contents that are available to them with the help of the Internet. Here, first of all, we mean social networks such as Facebook, Instagram or Tik Tok, but we also have in mind YouTube, which is a very popular medium where various contents are shown for the purposes of online teaching and information from the world of science, culture, social life of young people. Having in mind the mentioned facts, the research, the results of which will be presented in this paper, deals with the issue of conditionalconsequential connection between the use of English in third, fourth and fifth grade students of elementary school “Branko Radičević” in Kosovska Mitrovica and teaching and other content within online teaching, data for teaching purposes from the sources of the daily press in Serbia, the content of certain television programs as well as the mentioned sources of websites for the purposes of collecting information. In order to obtain relevant data, an online survey was made and conducted, within which words from the Serbian and English original vocabulary were offered in the given context of statements from the Serbian language. The aim of the study is to examine the frequency of use of anglicisms, ie words of foreign, English, origin, and to determine the cause-and-effect relationship with the offered internet media and their contents. We will show in the paper that the results of our study showed that the use of anglicisms is positively correlated with the time spent in research on social networks, and that the negative correlation of the use of anglicisms in relation to time spent in online classes organized during the state of emergency in Serbia in the first months of the Kovid virus epidemic 19.
Keywords: anglicisms; online teaching; primary school; students